Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1463-1326.2012.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

No pharmacokinetic interaction between ipragliflozin and sitagliptin, pioglitazone, or glimepiride in healthy subjects

Abstract: Ipragliflozin did not affect the pharmacokinetics of sitagliptin, pioglitazone or glimepiride and vice versa, suggesting that no dose-adjustments are likely to be required when ipragliflozin is given in combination with other glucose-lowering drugs in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…PK properties of ipragliflozin and sitagliptin, pioglitazone or glimepiride were investigated in three separate open-label, randomized, two-way crossover design trials in healthy subjects [31]. These studies demonstrated that acutely, administration of ipragliflozin to sitagliptin, pioglitazone or glimepiride does not change the PK [33] Fonseca et al [40] Wilding et al »31 kg/m 2 , T2DM diagnosis: »5 years) participated in a double-blind, randomized placebo-controlled trial conducted in multiple centers [33].…”
Section: Pks and Metabolismmentioning
confidence: 99%
“…PK properties of ipragliflozin and sitagliptin, pioglitazone or glimepiride were investigated in three separate open-label, randomized, two-way crossover design trials in healthy subjects [31]. These studies demonstrated that acutely, administration of ipragliflozin to sitagliptin, pioglitazone or glimepiride does not change the PK [33] Fonseca et al [40] Wilding et al »31 kg/m 2 , T2DM diagnosis: »5 years) participated in a double-blind, randomized placebo-controlled trial conducted in multiple centers [33].…”
Section: Pks and Metabolismmentioning
confidence: 99%
“…Ipragliflozin, a sodium-glucose co-transporter 2 inhibitor [1], improves glycaemic control by promoting urinary glucose excretion in patients with type 2 diabetes mellitus (T2DM) [2][3][4][5][6]. Western studies have shown that ipragliflozin in combination with metformin improves glycaemic control with a low incidence of adverse events [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, multiple doses of sitagliptin did not change the pharmacokinetics of a single dose of ipragliflozin (Table 5). Thus, no dose-adjustments are likely to be required when ipragliflozin is given in combination with sitagliptin in patients with T2D [69] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…To investigate the effect of ipragliflozin on the pharmacokinetics of sitagliptin and vice versa, ipragliflozin 150 mg and sitagliptin 100 mg were administered alone or in combination in two cohorts of 32 healthy subjects [69] . Multiple doses of ipragliflozin did not change the AUC inf and C max of a single dose of sitagliptin : geometric mean ratio (GMR) and 90% CI for AUC inf and C max , with and without ipragliflozin, were within the predefined range of 80-125 % (Table 5).…”
Section: Pharmacokineticsmentioning
confidence: 99%